A Note on Modified $k$-Pell Hybrid Numbers - Catari̇no, Paula Maria Machado Cruz; Bi̇lgi̇ci̇, Göksal (Mehmet Zeki SARIKAYA, 2020)
Modified $k$-Pell hybrid sequence is defined in this paper. The Binet formula and the generating functions for modified k-Pell hybrid numbers are also presented. By using the Binet formula, some properties involving this sequence, including Catalan's, Cassini's and d'Ocagne's identities, are obtained.
Keywords: Matematik; Modified $k$-Pell numbers; Hybrid numbers; Recurrence relations; Generating functions; Binet' s formula; Mathematical Sciences